Fixed exchange rates, independent central banks and price stability in postcommunist countries: Conservatism and credibility. (27th November 2013) - Bodea, Cristina
<x xml:space="preserve">Abstract</x> Central bank independence (CBI) and fixed exchange rates are used by governments to achieve stable prices. This article analyzes the mechanisms through which the two monetary institutions could work: Indirectly via a disciplinary effect on money growth rates or via an additional credibility effect on inflation expectations and the cost of capital. I further explain how both discipline and credibility are affected by the distinct flaws of independent central banks and fixed exchange rates: central banks lack transparency and fixed exchange rates take many shapes and are routinely devalued. The argument is tested with quarterly data from postcommunist countries for years 1991 to 2007. The findings show a strong disciplinary effect of monetary institutions on rates of M2 change and an effect on inflation controlling for money growth, but credibility does not extend to lower real short‐term market interest rates. Political institutions do condition the effect of central bank independence, while the types of fixed exchange rates affect money growth rates and inflation to different degrees.